Monte Cristo, era ouro, era prata, com a desapropriação todo mundo “mete a mão”: da instituição de “PA” à reivindicação de território quilombola - Ayres, Gardenia Mota (2015)
The work presented here is the result of Master's research of the Graduate Program in Social Cartography and Policy in the Amazonia. In the University of Maranhão of States. (UEMA) In partnership with the Program of Graduate Studies in Political Science from the Federal University of Minas Gerais (UFMG). The situation studied refers to, called by social agents, Territory Monte Cristo, located geographically in the region designated as "Baixada Maranhense" precisely the so-called county of Penalva (MA). This paper aims to conduct a review of the process of recognition of the Territory Monte Cristo. The study theme has presented his research locus in an ancient footprint that in the history of land concentration process undergoes intense conflicts with the designated farmers and alleged landowners. Thus, the territory called Monte Cristo, in the late nineteen hundred and seventy-eight goes through a complex process of buying and selling culminating in the expropriation of land for the creation of a settlement project. The expropriation turn not had results favorable to households already living in the territory there followed generations, but those supposed owners who felt authorized to extend its power of coercion, promoting acceleration in sales of land and the privatization of natural resources, indispensable to families living in the communities referred to the territory. The Communities, through their organizational resources, trigger the collective identity and claim the territory as titration quilombola, backed by constitutional guarantees, built by intense process of political mobilization of social movements. The imposition of borders with the expropriation intensified internal conflicts and threatens the specific territoriality claimed by social agents, through the process of territorial built by the groups. Thus, I present the various contradictions in the process of recognition of Monte Cristo, showing the action of the State in settlement project institution of land reform given the claim of the groups by titration of the quilombo territory.